. The two-hierarchical structural slotting to improve the information’s integrity in telecommunication systems - Бараннік, В. В.; Підлісний, С. А.; Олешко, Т. І. (Science-based technologies, 2017)
The article substantiates the problem of the integrity ensure for the state video information resource in modern image processing methods at the state institutions. There is the analysis of the existing error localization technologies in the recovery process. It is proposed to develop an equalization redistribution method for statistical codes in order to ensure code positioning. The binary elements sequence structural characterization accounted in the fixed-length code constructs (slots) formation. The two-hierarchical scheme structural slotting conducting is proposed due to the binomial code formation nature. The recovery error propagation localization within the binary elements sequence set that has certain structural characteristics is justified. It is proposed to use the last binomial code forming feature for positioning transforms in of cyber attack conditions. Thus, the two-hierarchical structural slotting method with variable length codes redistribution has been developed. It allows increasing the state video information resource integrity. The scientific and applied research direction is defined: the image processing time costs reduction taking into the codes stream structural features account and the state video information resource confidentiality increasing with binominal coding.